The self-assessment and accreditation process of the Bachelor's degree in Social Studies and Civic Education, an initial step to improve the teaching of the discipline. - Zárate Montero, María Jesús (2014)
In this article, the authors analyze the importance of the process of accreditation  for the improvement of the quality of the university education on having taken the particular case of the Baccalaureate as a reference in the Bachillerato en la Enseñanza  de los Estudios Sociales y Educación Cívica (BEESEC), in the Universidad Nacional,  career that after an exhaustive process of analysis manages to obtain, in October, 2013, the official accreditation on the part of the National System of Accreditation of the Top  Education (SINAES). His character is rather reflexive and raises how the realized effort  represents the base in order that, of progressive and systematic form, with long-term vision the career meets strengthened from the academic and administrative point of view.